Validity of Quinpirole Sensitization Rat Model of OCD: Linking Evidence from Animal and Clinical Studies - Stuchlik, Ales; Radostová, Dominika; Hatalova, Hana; Vales, Karel; Nekovarova, Tereza; Koprivova, Jana; Svoboda, Jan; Horacek, Jiri (Frontiers in Behavioral Neuroscience, 2016)
Obsessive-compulsive disorder (OCD) is a neuropsychiatric disorder with 1-3% prevalence. OCD is characterized by recurrent thoughts (obsessions) and repetitive behaviors (compulsions). The pathophysiology of OCD remains unclear, stressing the importance of pre-clinical studies. The aim of this article is to critically review a proposed animal model of OCD that is characterized by the induction of compulsive checking and behavioral sensitization to the D2/D3 dopamine agonist quinpirole.. Changes in this model have been reported at the level of brain structures, neurotransmitter systems and other neurophysiological aspects. In this review, we consider these alterations in relation to the clinical manifestations in OCD, with the aim to discuss and evaluate axes of validity of this model. Our analysis shows that some axes of validity of quinpirole sensitization model (QSM) are strongly supported by clinical findings, such as behavioral phenomenology or roles of brain structures. Evidence on predictive validity is contradictory and ambiguous. It is concluded that this model is useful in the context of searching for the underlying pathophysiological basis of the disorder because of the relatively strong biological similarities with OCD.